Affordable housing policy: implications and prospects for low-income communities in Indonesia - Data Wardana; Syafhendry Syafhendry; Mendra Wijaya; Abdul Aziz (Otoritas : Jurnal Ilmu Pemerintahan, 2025)
The inconsistency between Law No. 1 of 2011 on Housing and Settlement Areas and Law No. 23 of 2014 on Regional Government has led to challenges in managing housing and settlement affairs, particularly with the introduction of the Workers' Housing Savings Scheme. This policy mandates workers to contribute to a housing savings program to facilitate home ownership. However, housing and settlement issues are considered mandatory public services, as the state is responsible for fulfilling the basic needs of its citizens. This article employs a qualitative research methodology, utilizing literature studies and policy document analysis to examine the role of local governments in implementing affordable housing provisions within the central government's national housing program. The findings indicate that existing housing policies, particularly, have not effectively addressed the housing needs of workers, as the financial burden of regular contributions or salary deductions is significant. Although government housing programs are designed to support homeownership, they have become an additional financial burden rather than a viable solution. On the other hand, various government subsidy programs, such as the One Million Houses Program, have shown positive results in providing affordable housing. This collaborative initiative between the government and housing developers aims to accelerate housing construction, demonstrating a growing trend in addressing the housing backlog. The article concludes that optimizing existing government housing programs and policies is crucial for enhancing housing accessibility and alleviating the financial burden on low-income workers.